mTOR promotes the formation and growth of tertiary lymphoid tissues in the kidney - Atwood, Daniel J.; He, Zhibin; Miyazaki, Makoto; Hopp, Katharina; Jani, Alkesh; Furgeson, Seth B.; Faubel, Sarah; Edelstein, Charles L. (Frontiers in Immunology, 2025)
Tertiary lymphoid tissues (TLTs) are ectopic lymphoid tissues that form de novo in nonlymphoid organs. In this study, we demonstrate that the kidneys of aged mice with a renal tubule-specific knockout of autophagy-related 7 (Atg7) contain numerous and large TLTs. p-S6 protein, a marker of mTORC1, was elevated in the tubules adjacent to the TLTs as well as within the TLTs themselves. In Atg7−/− kidneys, tubular injury and increased proinflammatory cytokines were observed, both of which are known to promote TLT formation and growth. In mice with either polycystic kidney disease (Pkd1RC/RC) or kidney ischemia, increased p-S6 was observed in tubules near TLTs and within the TLTs. Treatment with Torin2, an mTOR inhibitor, led to the virtual disappearance of TLTs in Pkd1RC/RC kidneys and a significant reduction in TLTs in ischemic kidneys. To assess whether p-S6 in the tubules was driving TLT formation, ischemia was induced in tubule-specific Atg7−/− Raptor (mTORC1)−/− mice. The tubule-specific Raptor knockout had little effect on the TLTs. In summary, Torin2, which inhibited p-S6 in both tubules and TLTs, resulted in a large decrease in TLTs in ischemic and Pkd1RC/RC kidneys. Tubule-specific knockout of mTORC1 (Raptor) had no effect on TLTs. In conclusion, p-S6 activity within the TLTs, rather than in the tubules, drives the proliferation of immune cells and the formation and growth of TLTs. These findings provide new insights into the role of mTOR in TLT development. The study has important therapeutic implications, as TLTs are involved in numerous disease processes and mTOR inhibitors are widely used in clinical practice.